2016
DOI: 10.2298/gensr1603827h
|View full text |Cite
|
Sign up to set email alerts
|

Correlation and path analysis of yield and yield components of confectionary sunflower

Abstract: Path coefficient analysis was applied to gain information on direct and indirect effects of studied traits (seed oil content, kernel oil content, seed protein content, kernel protein content, head diameter, kernel ratio and plant height) on sunflower seed yield. Traits which exhibit the highest effects on seed yield will be used as a selection criterion in confectionary sunflower breeding. The research was conducted during three vegetation seasons on 22 experimental confectionary sunflower hybrids, created in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 10 publications
0
10
1
Order By: Relevance
“…BALALIĆ et al (2012) reported a significant correlation between seed yield, oil yield and oil content. While HLADNI et al (2016) reported a significant correlation between protein content and yield in confectionary sunflower. SUPRIYA et al (2017) concluded that simultaneous improvement in two or more parameters of seed yield is possible when positive correlations are observed.…”
Section: Correlationmentioning
confidence: 95%
“…BALALIĆ et al (2012) reported a significant correlation between seed yield, oil yield and oil content. While HLADNI et al (2016) reported a significant correlation between protein content and yield in confectionary sunflower. SUPRIYA et al (2017) concluded that simultaneous improvement in two or more parameters of seed yield is possible when positive correlations are observed.…”
Section: Correlationmentioning
confidence: 95%
“…Before establishing the simplified RWU model, stepwise regression analysis was utilized to screen the independent variables initially. However, the simple correlation coefficient did not provide a comprehensive link between the tested indicators and the RWU (Hladni, Jocic, Mijic, Miklic, & Miladinovic, 2016). Therefore, the correlation coefficient was further analyzed using a path analysis (Wright, 1921) that included the direct and indirect effects (Astereki, Sharifi, & Pouresmael, 2017).…”
Section: Path Analysismentioning
confidence: 99%
“…The threshold for marginal crops and medicinal plants like fenugreek has been higher due to low attention as more resources are allocated for staple and commercial crops (ACHARYA et al, 2006). The various biochemical and molecular methods play a key role in the identification of diverse crop genotypes (NIKOLIC et al, 2016;HLADNI et al, 2016;CHANDRAWATI et al, 2016;PERIC et al, 2014). In the present study a geographically diverse fenugreek population was evaluated for a range of agro-morphological and phonological diversity along with total seed protein variation.…”
Section: Morphologicalmentioning
confidence: 99%